Meteorological Connectivity from Regions of High Biodiversity within the McMurdo Dry Valleys of Antarctica - Katurji, Marwan; Khan, B.; Sprenger, Michael; Datta, R.; Joy, K.; Zawar-Reza, Peyman; Hawes, Ian (Journal of Applied Meteorology and Climatology, 2019)
ISSN:1558-8424 ISSN:0733-3021 ISSN:0021-8952 ISSN:0894-8763 ISSN:1558-8432